THE STABILITY OF FINANCIAL SYSTEM OF AZERBAIJAN DURING THE GLOBAL FINANCIAL CRISIS - R. Guliyev (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The work describes in details the elements of the financial system of Azerbaijan. The impact of the global financial crisis on the economy of the country is studied. The reasons of stable development of the financial system of the country are listed.